2006
DOI: 10.1111/j.1099-1123.2006.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Banks on Company Auditor Choice: The Case of Japan

Abstract: The purpose of the paper is to examine the auditor services market in Japan in 2000. We used a sample of 1,485 companies listed on the Tokyo Stock Exchange. We found that auditor mix within the client base was dependent on the main bank. There was evidence that in some cases companies had a tendency to choose their main bank's preferred auditor. We also found that the market was dominated by four audit firms: Shin Nihon, ChuoAoyama, Asahi and Tohmatsu. These four firms collectively audited 81% of the companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Velury, Reisch, and O'Reilly () found that choice of industry‐specialist auditors is associated with level of institutional ownership. Pong and Kita () sampled companies listed on the Tokyo Stock Exchange and suggested that the main banks appoint a preferred auditor who frequently owns shares in companies and is often one of the largest shareholders of a public firm. Also, Kane and Velury () found consistent evidence that institutional ownership is positively associated with auditor size.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
“…Velury, Reisch, and O'Reilly () found that choice of industry‐specialist auditors is associated with level of institutional ownership. Pong and Kita () sampled companies listed on the Tokyo Stock Exchange and suggested that the main banks appoint a preferred auditor who frequently owns shares in companies and is often one of the largest shareholders of a public firm. Also, Kane and Velury () found consistent evidence that institutional ownership is positively associated with auditor size.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
“…Partners with established relationships with clients remain both partners and shareholders for many years, there being no enforced retirement age. Such obvious dedication by partners to their accounting firms helps to maintain strong and long-standing personal relationships with clients and their stakeholders (banks) (Pong and Kita, 2006).…”
Section: Following the West: Introduction Of Auditing And The Accountmentioning
confidence: 99%
“…Japan is no exception to the dangers of weak gatekeeping due to client capture in professional services. In auditing, for example, audit firms tended to follow the lead of main banks, whose corporate clients might choose an audit firm that they think their main bank would prefer (Matsubara & Endo, 2018;Pong & Kita, 2006). By the 2000s, shifts in government policy led to the Financial Services Agency to insist on stricter audit services (as seen by its unprecedented action to suspend ChuoAoyama and to criminally indict its partners for their role in the Kanebo accounting fraud in 2006 (Skinner & Srinivasan, 2012).…”
mentioning
confidence: 99%